Acid and alkali resistant protective film and preparation method thereof

By combining PET, PA6, PP and other materials with nanosilicon dioxide, modified polypropylene fibers, etc., an acid-base-resistant protective film is prepared, which solves the problem of easy wear of traditional PET protective films and achieves higher mechanical properties and service life.

CN118496633BActive Publication Date: 2025-04-15深圳国兴祥胶粘材料有限公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410618398.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-17
Publication Date
2025-04-15
Estimated Expiration
2044-05-17

AI Technical Summary

Technical Problem

Traditional PET protective films can easily cause surface wear when rubbing with other objects, affecting their service life.

Method used

The acid-base-resistant protective film is prepared by melt extrusion and casting film forming processes using the combination of materials such as PET, PA6, PP, methyl methacrylate-butadiene-styrene copolymer, compatibility agent, nanosilica, modified polypropylene fiber, pretreated ceramide and modified diatomaceous earth.

Benefits of technology

It improves the mechanical properties, scratch resistance and wear resistance of the protective film, extends the service life, and has good chemical stability and thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004845961160000101
    Figure BDA0004845961160000101
  • Figure BDA0004845961160000111
    Figure BDA0004845961160000111
Patent Text Reader

Abstract

The present application relates to the technical field of protective film materials, and specifically discloses an acid- and alkali-resistant protective film and a preparation method thereof. The acid- and alkali-resistant protective film includes the following raw materials: 80-90 parts of PET, 35-45 parts of PA6, 30-40 parts of PP, 3-5 parts of methyl methacrylate-butadiene-styrene copolymer, 1-3 parts of compatibilizer, 10-15 parts of nano-silicon dioxide, 8-12 parts of modified polypropylene fiber, 2-5 parts of pretreated ceramsite, and 12-18 parts of modified diatomaceous earth; the preparation method of pretreated ceramsite: crush the ceramsite, calcine at a temperature of 280-300°C, and obtain pretreated ceramsite, and the diameter of the pretreated ceramsite is 0.05-0.08mm. The acid- and alkali-resistant protective film prepared in the present application has good mechanical properties, wear resistance and scratch resistance. When the PET protective film rubs against other objects, it is not easy to cause surface wear, thereby increasing the service life of the PET protective film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of protective film materials, and more specifically, to an acid- and alkali-resistant protective film and a preparation method thereof. Background Art

[0002] PET protective film is a polyester film with a smooth surface and good transparency. It has many excellent properties such as moisture-proof, waterproof, dust-proof, and anti-static. According to its use, it can be divided into food preservative protective film, digital product protective film, car protective film, and household protective film. It is used in all walks of life because of its convenience and low price.

[0003] Traditional PET protective films usually melt PET raw materials and then make the molten PET material into a film through processes such as extrusion, stretching and winding. However, PET protective films made only from PET raw materials are prone to surface wear when rubbed against other objects, which in turn affects the service life of the PET protective film. Summary of the invention

[0004] In order to improve the problem that the PET protective film prepared using only PET raw materials is prone to surface wear, the present application provides an acid- and alkali-resistant protective film and a preparation method thereof.

[0005] In a first aspect, the present application provides an acid- and alkali-resistant protective film, which adopts the following technical solution:

[0006] An acid- and alkali-resistant protective film comprises the following raw materials, measured by weight: 80-90 parts of PET, 35-45 parts of PA6, 30-40 parts of PP, 3-5 parts of methyl methacrylate-butadiene-styrene copolymer, 1-3 parts of a compatibilizer, 10-15 parts of nano-silicon dioxide, 8-12 parts of modified polypropylene fiber, 2-5 parts of pretreated ceramsite, and 12-18 parts of modified diatomaceous earth;

[0007] The preparation method of the pretreated ceramsite comprises the following steps: crushing the ceramsite, calcining the ceramsite at a temperature of 280-300° C. for 1-2 hours, and obtaining the pretreated ceramsite, wherein the diameter of the pretreated ceramsite is 0.05-0.08 mm.

[0008] By adopting the above technical scheme, PET has high transparency, good mechanical properties, chemical stability, acid and alkali resistance and thermal stability, PA6 has good mechanical strength, good toughness, high tensile strength, compressive strength, scratch resistance, acid and alkali resistance and wear resistance, the compatibilizer can form a thin film between PET and PA6, improve the compatibility and dispersibility between PET and PA6, make the modified polypropylene fiber and modified diatomaceous earth evenly dispersed in the system, thereby improving the mechanical properties, wear resistance and heat resistance of the system; the PP film has anti-scratch and wear resistance, excellent mechanical properties, strong bending fatigue resistance, strong plasticity, acid and alkali resistance, the addition of PP can improve the crystallization performance, impact, environmental stress cracking resistance, water resistance and processing performance of PET, and obtain a high modulus and high impact resistance product; the compatibilizer makes PET, PA6 and PP mixed evenly, and the combination of PET, PA6 and PP has good strength, impact resistance, wear resistance and scratch resistance, thereby making the prepared protective film have a good service life.

[0009] Methyl methacrylate-butadiene-styrene copolymer has good toughness, good wear resistance and impact resistance. When mixed with PET, PA6 and PP, it improves the transparency, toughness, impact resistance, wear resistance, corrosion resistance, high temperature resistance and easy processing of the system. Nano-silicon dioxide is light-transmissive and has a small particle size, which can make the protective film denser and improve the transparency, strength, wear resistance, scratch resistance and toughness of the protective film. Modified polypropylene fiber is light, high-strength, elastic, wear-resistant, corrosion-resistant, high tensile strength and aging resistance. The modified polypropylene fiber is evenly dispersed in the system, which improves the wear resistance and mechanical properties of the system. The pretreated expanded clay has a large specific surface area, light weight, high strength, good corrosion resistance and good wear resistance, and can be evenly dispersed in the system to improve the wear resistance of the system; the modified diatomaceous earth has a porous structure, good air permeability and adsorption, and can improve the heat resistance, wear resistance, anti-aging and other properties of the system. Nano-silicon dioxide can be loaded on the surface and pores of modified polypropylene fibers and modified diatomaceous earth, thereby improving the strength, wear resistance and scratch resistance of modified polypropylene fibers and modified diatomaceous earth. It is then evenly mixed with PET, PA6 and PP to improve the mechanical strength, scratch resistance, wear resistance and other corresponding properties of the system.

[0010] Optionally, the method for preparing the modified polypropylene fiber comprises the following steps:

[0011] (1) dispersing polypropylene fibers in a sodium hypochlorite solution, soaking for 1-3 minutes, washing with water, and then heating at 200-210° C. for 1-2 hours to obtain pretreated polypropylene fibers;

[0012] (2) dissolving PVA in deionized water to obtain a PVA solution, and then spraying it on the surface of the polypropylene fiber pretreated in step (1) to obtain treated polypropylene fiber, and then dispersing ZIF-8 in methanol, stirring evenly, spraying it on the surface of the treated polypropylene fiber, drying, and setting aside;

[0013] (3) dispersing the modified silver nanowires in an ethanol solution, stirring at a temperature of 50-55° C. for 30-40 minutes, then soaking the polypropylene fiber obtained in step (2) in the ethanol solution of the silver nanowires for 60-80 seconds, taking out the polypropylene fiber, and drying it to obtain a modified polypropylene fiber;

[0014] The modified silver nanowire has a diameter of 70-90 nm and a length of 70-80 μm.

[0015] By adopting the above technical scheme, the surface of the polypropylene fiber is treated with a sodium hypochlorite solution to remove organic impurities on the surface of the polypropylene fiber, so that grooves appear on the surface of the polypropylene fiber, thereby increasing the specific surface area of ​​the polypropylene fiber. Heating is further used to remove impurities to obtain pretreated polypropylene fibers with multiple grooves on the surface.

[0016] PVA solution has good adhesiveness and film-forming properties. When the PVA solution is sprayed on the surface of the polypropylene fiber, the PVA forms a film on the surface of the polypropylene fiber to coat the polypropylene fiber, thereby improving the mechanical properties, crack resistance, tensile strength, acid and alkali resistance and durability of the polypropylene fiber.

[0017] ZIF-8 is a metal-organic framework material with a unique pore structure. It has a high specific surface area, regular pore structure, high chemical stability and thermal stability. When ZIF-8 is sprayed on the surface of polypropylene fiber, ZIF-8 is better bonded to the surface of polypropylene fiber through PVA, which improves the mechanical strength, wear resistance and adsorption of polypropylene fiber, which will help the further processing of polypropylene fiber.

[0018] The modified silver nanowires have nanoscale size effect, excellent light transmittance, flexibility, antibacterial property, wear resistance and flexibility. The polypropylene fiber is immersed in the ethanol solution of the silver nanowires, so that the modified silver nanowires are loaded on the surface of the polypropylene fiber. The modified silver nanowires and ZIF-8 are both adhered to the surface of the polypropylene fiber through PVA. At the same time, the modified silver nanowires are also loaded on the surface and pores of ZIF-8, which improves the antibacterial property, flexibility and wear resistance of the polypropylene fiber. The modified polypropylene fiber is subsequently used in the protective film to improve the mechanical properties, flexibility, wear resistance and antibacterial property of the protective film, which is helpful for the durable application of the protective film.

[0019] Optionally, the mass ratio of the polypropylene fiber, ZIF-8 and modified silver nanowire is 1:0.1-0.3:0.2-0.5.

[0020] By adopting the above technical scheme, the mass ratio of polypropylene fiber, ZIF-8 and modified silver nanowires is further limited within a certain range, so that the modified polypropylene fiber has higher mechanical properties, wear resistance and antibacterial properties, ZIF-8 can be loaded on the surface and pore structure of polypropylene fiber, and the modified silver nanowires can be loaded on the surface and pore structure of polypropylene fiber and ZIF-8. The polypropylene fiber, ZIF-8 and silver nanowires cooperate with each other to improve the mechanical properties, wear resistance and antibacterial properties of the polypropylene fiber. The subsequently modified polypropylene fiber is applied to the protective film, thereby improving the corresponding performance of the protective film.

[0021] Optionally, the preparation of the modified silver nanowires comprises the following steps: dispersing the silver nanowires in ethanol, ultrasonicating for 15-20 minutes, adding graphene, continuing ultrasonicating, then adding a silane coupling agent, stirring at a temperature of 60-70°C for 1-2 hours, stirring evenly, and drying to obtain modified silver nanowires.

[0022] By adopting the above technical scheme, graphene has high strength, large specific surface area and high wear resistance, silver nanowires can be loaded on the surface of graphene, thereby improving the wear resistance and strength of the silver nanowires, and the silane coupling agent can react with the hydroxyl groups on the surface of the silver nanowires, and also react with the hydroxyl groups or carboxyl groups on the surface of the graphene, so that the silver nanowires and graphene are tightly connected, thereby improving the mechanical strength and wear resistance of the silver nanowires, and subsequently applied to the preparation of modified polypropylene fibers, so that the pretreated silver nanowires can be stably loaded on the surface of the polypropylene fibers, thereby improving the corresponding properties of the polypropylene fibers.

[0023] In addition, silver nanowires are prone to agglomeration and oxidation reaction with oxygen in the air, which is not conducive to the storage of silver nanowires. The surface of the silver nanowires is treated with a silane coupling agent. The silane coupling agent reacts with the silver nanowires so that the silane coupling agent coats the silver nanowires, making the silver nanowires less likely to agglomerate and oxidize, and improving the dispersibility of the silver nanowires; the silane coupling agent reacts with the groups on the surface of graphene, so that the graphene is dispersed in the solution, thereby improving the dispersibility and stability of the graphene.

[0024] Optionally, the mass ratio of the silver nanowires, the silane coupling agent and the graphene is 1:0.03-0.05:0.6-0.9.

[0025] By adopting the above technical scheme, the mass ratio of silver nanowires, silane coupling agent and graphene is further limited within a certain range, thereby improving the mechanical strength and wear resistance of the silver nanowires, and the silver nanowires can be loaded on the surface of the graphene. The silane coupling agent reacts with the silver nanowires and the graphene respectively, thereby making the silver nanowires and the graphene tightly connected, thereby improving the mechanical strength and wear resistance of the silver nanowires. The subsequent application in the modification of polypropylene fibers enables the pretreated silver nanowires to be stably loaded on the surface of the polypropylene fibers, thereby improving the corresponding performance of the polypropylene fibers.

[0026] Optionally, the method for preparing the modified diatomite comprises the following steps:

[0027] (1) pulverizing diatomaceous earth, sieving, dispersing in deionized water, adding sodium polyacrylate, stirring for 30-35 minutes, and drying to obtain pretreated diatomaceous earth;

[0028] (2) dispersing nano-TiO2 in an ethanol aqueous solution, adding a titanate coupling agent, ultrasonicating at a temperature of 55-60° C. for 1-1.5 h, filtering, and drying to obtain treated nano-TiO2;

[0029] (3) Dispersing the diatomite pretreated in step (1) in deionized water, adding the nano-TiO2 treated in step (2), stirring for 1-2 hours, drying, then spraying the modified chitosan solution, drying, and obtaining modified diatomite.

[0030] By adopting the above technical solution, the diatomite has a porous structure, a large specific surface area and is covered with a large number of silanol groups on the surface. Sodium polyacrylate has good hydrophilicity and stability and can form a gel in water, which improves the viscosity and elasticity of the diatomite and facilitates the subsequent treatment of the diatomite.

[0031] Nano-TiO2 and titanate coupling agent are mixed, and the titanate coupling agent combines with the surface hydroxyl groups of nano-TiO2 in the form of chemical bonds, which improves the dispersibility of nano-TiO2 and helps the subsequent stability of nano-TiO2. At the same time, the titanate coupling agent also improves the mechanical properties and impact resistance of nano-TiO2, which helps the corresponding properties of the subsequent modified diatomite.

[0032] The diatomite pretreated in step (1) and the nano-TiO2 treated in step (2) are mixed evenly, the nano-TiO2 can be loaded on the surface of the diatomite, the titanate coupling agent can react with the hydroxyl group on the surface of the diatomite, and the sodium polyacrylate can increase the viscosity of the system, so that the diatomite, the nano-TiO2 and the titanate coupling agent are tightly bonded, and finally dried, and then the modified chitosan solution is sprayed. The modified chitosan solution has good film-forming properties and can coat the diatomite, further allowing the nano-TiO2 to be stably loaded on the surface of the diatomite, thereby improving the mechanical strength and wear resistance of the diatomite, and is subsequently applied to the protective film, in combination with other components, to improve the mechanical properties and wear resistance of the protective film.

[0033] Optionally, the mass ratio of the diatomite, nano-TiO2 and titanate coupling agent is 1:0.3-0.5:0.06-0.08.

[0034] By adopting the above technical scheme, the mass ratio of diatomite, nano-TiO2 and titanate coupling agent is further limited within a certain range, thereby improving the mechanical strength and wear resistance of diatomite. Diatomite, nano-TiO2 and titanate coupling agent have a synergistic effect. Nano-TiO2 can be loaded on the surface of diatomite, thereby improving the wear resistance of diatomite. Titanate coupling can react with diatomite and nano-TiO2, thereby making the connection between diatomite and nano-TiO2 more stable, thereby further improving the mechanical properties of diatomite. Subsequently, the modified diatomite is applied to a protective film, and the modified diatomite is mixed with modified polypropylene fiber and nano-silicon dioxide, thereby further improving the adhesion between the components, thereby improving the mechanical strength and wear resistance of the protective film.

[0035] Optionally, the method for preparing the modified chitosan solution comprises the following steps: dispersing chitosan in deionized water, adding hydrochloric acid, adjusting the pH to 4-5, stirring for 10-20 minutes to dissolve the chitosan, then adding sodium alginate and nano bamboo fiber, stirring evenly, and obtaining a modified chitosan solution;

[0036] The length of the nano bamboo fiber is 25-30 μm and the diameter is 10-15 nm.

[0037] By adopting the above technical scheme, chitosan is dissolved in a hydrochloric acid aqueous solution, sodium alginate and chitosan undergo a cross-linking reaction to form a stable gel system, thereby improving the viscosity of the solution. After the chitosan is subsequently formed into a film, the stability and mechanical properties of the film are improved. The nano bamboo fiber has high strength, high toughness, low density, good corrosion resistance and wear resistance, and can be uniformly dispersed in the chitosan gel system. After the chitosan is subsequently formed into a film, the mechanical properties and wear resistance of the film are improved. The modified chitosan solution is sprayed on the pretreated diatomaceous earth surface, so that the diatomaceous earth and nano-TiO2 are stably bonded together, thereby improving the mechanical properties and wear resistance of the modified diatomaceous earth, and thus facilitating the subsequent application of the modified diatomaceous earth.

[0038] Optionally, the mass ratio of chitosan, sodium alginate and nano bamboo fiber is 1:0.1-0.2:0.06-0.08.

[0039] By adopting the above technical scheme, the mass ratio of chitosan, sodium alginate and nano bamboo fiber is further limited within a certain range, thereby improving the mechanical properties and wear resistance of chitosan after film formation. Sodium alginate and chitosan undergo a cross-linking reaction to form a stable gel system. Nano bamboo fiber is evenly dispersed in the gel system of chitosan. After subsequent chitosan film formation, the mechanical properties and wear resistance of the film are improved, and it is subsequently applied to modified diatomaceous earth, thereby improving the corresponding properties of diatomaceous earth.

[0040] In the second aspect, the present application provides a method for preparing an acid and alkali resistant protective film, comprising the following steps: stirring PET, PA6, PP, methyl methacrylate-butadiene-styrene copolymer, compatibilizer, nano-silica, modified polypropylene fiber, pretreated ceramsite, and modified diatomaceous earth at a temperature of 90-95°C, melt-extruding, and casting to form a film to obtain an acid and alkali resistant protective film.

[0041] By adopting the above technical scheme, the acid-base resistant protective film prepared by the above method has good mechanical properties, scratch resistance and wear resistance, and is easy to operate.

[0042] In summary, this application has the following beneficial effects:

[0043] 1. In the present application, PET has high transparency, good mechanical properties, chemical stability, acid and alkali resistance and thermal stability; PA6 has good mechanical strength, good toughness, high tensile strength, compressive strength, scratch resistance, acid and alkali resistance and wear resistance; PP film has scratch resistance and wear resistance, excellent mechanical properties, strong resistance to bending fatigue, strong plasticity and acid and alkali resistance; the compatibilizer makes PET, PA6 and PP mixed evenly; PET, PA6 and PP have good strength, impact resistance, wear resistance and scratch resistance, so that the prepared protective film has a good service life.

[0044] 2. The nano-silicon dioxide in this application is light-transmitting and has a small particle size, which can make the protective film denser and improve the transparency, strength, wear resistance, scratch resistance and toughness of the protective film. The modified polypropylene fiber is light in weight, high in strength, elastic, wear-resistant, corrosion-resistant, has high tensile strength and aging resistance. The modified polypropylene fiber is evenly dispersed in the system, which improves the corresponding properties such as the wear resistance and mechanical properties of the system. The pretreated ceramsite has a large specific surface area, light weight, high strength, good corrosion resistance and good wear resistance, and can be evenly dispersed in the system to improve the wear resistance of the system.

[0045] 3. The modified diatomaceous earth in the present application has a porous structure, good air permeability and adsorption, which can improve the heat resistance, wear resistance, aging resistance and other properties of the system. Nano-silicon dioxide can be loaded on the surface and pores of modified polypropylene fiber and modified diatomaceous earth, thereby improving the strength, wear resistance and scratch resistance of modified polypropylene fiber and modified diatomaceous earth. Subsequently, it is evenly mixed with PET, PA6 and PP, thereby improving the corresponding properties such as mechanical strength, scratch resistance and wear resistance of the system. DETAILED DESCRIPTION

[0046] Preparation example of modified polypropylene fiber

[0047] Preparation Example 1-1

[0048] The preparation method of modified polypropylene fiber comprises the following steps:

[0049] (1) dispersing 1.2 kg of polypropylene fiber in 2 L of a 3% sodium hypochlorite solution, soaking for 2 min, washing with water, and then heating at 210° C. for 1.5 h to obtain pretreated polypropylene fiber;

[0050] (2) dissolving 0.01 kg of PVA in deionized water to obtain a PVA solution with a concentration of 0.01 kg / L, and then spraying the solution on the surface of the polypropylene fiber pretreated in step (1) to obtain treated polypropylene fiber, and then dispersing ZIF-8 (purchased from Shanghai Koraman Reagent Co., Ltd.) in 0.5 L of methanol, stirring evenly, spraying the solution on the surface of the treated polypropylene fiber, drying, and setting aside;

[0051] (3) dispersing the modified silver nanowires in 1.2 L of ethanol solution, stirring at 55° C. for 35 min, then soaking the polypropylene fiber obtained in step (2) in the ethanol solution of the silver nanowires for 70 s, taking out the polypropylene fiber, and drying it to obtain a modified polypropylene fiber;

[0052] The diameter of the modified silver nanowires is 70-90 nm and the length is 70-80 μm.

[0053] The mass ratio of polypropylene fiber, ZIF-8 and modified silver nanowires is 1:0.1:0.2.

[0054] The preparation of modified silver nanowires includes the following steps: dispersing 0.6 kg of silver nanowires in 1.3 L of ethanol, ultrasonicating for 20 minutes, adding graphene, continuing ultrasonicating for 1 hour, then adding silane coupling agent KH570, stirring at a temperature of 65° C. for 2 hours, stirring evenly, and drying to obtain modified silver nanowires.

[0055] The mass ratio of silver nanowires, silane coupling agent KH570 and graphene is 1:0.03:0.9.

[0056] Preparation Example 1-2

[0057] The difference from Preparation Example 1-1 is that ZIF-8 is not added.

[0058] Preparation Example 1-3

[0059] The difference from Preparation Example 1-1 is that no modified silver nanowires are added.

[0060] Preparation Example 1-4

[0061] The difference from Preparation Example 1-1 is that the mass ratio of polypropylene fiber, ZIF-8 and modified silver nanowire is 1:0.3:0.5.

[0062] Preparation Example 1-5

[0063] The difference from Preparation Example 1-1 is that the mass ratio of polypropylene fiber, ZIF-8 and modified silver nanowire is 1:0.6:0.1.

[0064] Preparation Example 1-6

[0065] The difference from Preparation Example 1-1 is that graphene is not added in the preparation of the modified silver nanowires.

[0066] Preparation Example 1-7

[0067] The difference from Preparation Example 1-1 is that the silane coupling agent KH570 is not added in the preparation of the modified silver nanowires.

[0068] Preparation Example 1-8

[0069] The difference from Preparation Example 1-1 is that the mass ratio of silver nanowires, silane coupling agent and graphene is 1:0.05:0.6.

[0070] Preparation Example 1-9

[0071] The difference from Preparation Example 1-1 is that the mass ratio of silver nanowires, silane coupling agent and graphene is 1:0.08:0.2.

[0072] Preparation example of modified diatomite

[0073] Preparation Example 2-1

[0074] The preparation method of modified diatomite comprises the following steps:

[0075] (1) 1 kg of diatomaceous earth was crushed, passed through a 20-mesh sieve, dispersed in 1.8 L of deionized water, 0.1 kg of sodium polyacrylate was added, stirred for 35 min, and dried to obtain pretreated diatomaceous earth;

[0076] (2) dispersing nano-TiO2 in 1.1 L of 75% ethanol aqueous solution, adding titanate coupling agent GR-201, ultrasonicating at 60°C for 1.5 h, filtering, and drying to obtain treated nano-TiO2;

[0077] (3) Disperse the diatomaceous earth pretreated in step (1) in 1.5 L of deionized water, add the nano-TiO2 treated in step (2), stir for 2 h, dry, then spray 0.2 kg of modified chitosan solution, dry, and obtain modified diatomaceous earth.

[0078] The mass ratio of diatomite, nano-TiO2 and titanate coupling agent GR-201 is 1:0.3:0.08.

[0079] The preparation method of the modified chitosan solution comprises the following steps: dispersing 0.2 kg of chitosan in 0.9 L of deionized water, adding hydrochloric acid, adjusting the pH to 5, stirring for 15 minutes to dissolve the chitosan, then adding sodium alginate and nano bamboo fiber, stirring evenly, and obtaining a modified chitosan solution;

[0080] The length of nano bamboo fibers is 25-30 μm and the diameter is 10-15 nm.

[0081] The mass ratio of chitosan, sodium alginate and nano bamboo fiber is 1:0.1:0.08.

[0082] Preparation Example 2-2

[0083] The difference from Preparation Example 2-1 is that no nano-TiO2 is added.

[0084] Preparation Example 2-3

[0085] The difference from Preparation Example 2-1 is that no titanate coupling agent is added.

[0086] Preparation Example 2-4

[0087] The difference from Preparation Example 2-1 is that the modified chitosan solution is not sprayed.

[0088] Preparation Example 2-5

[0089] The difference from Preparation Example 2-1 is that the mass ratio of diatomaceous earth, nano-TiO2 and titanate coupling agent is 1:0.5:0.06.

[0090] Preparation Example 2-6

[0091] The difference from Preparation Example 2-1 is that the mass ratio of diatomaceous earth, nano-TiO2 and titanate coupling agent is 1:0.8:0.01.

[0092] Preparation Example 2-7

[0093] The difference from Preparation Example 2-1 is that sodium alginate is not added in the preparation method of the modified chitosan solution.

[0094] Preparation Example 2-8

[0095] The difference from Preparation Example 2-1 is that in the preparation method of the modified chitosan solution, no nano bamboo fiber is added.

[0096] Preparation Example 2-9

[0097] The difference from Preparation Example 2-1 is that the mass ratio of chitosan, sodium alginate and nano bamboo fiber is 1:0.2:0.06.

[0098] Preparation Example 2-10

[0099] The difference from Preparation Example 2-1 is that the mass ratio of chitosan, sodium alginate and nano bamboo fiber is 1:0.4:0.01.

[0100] Example

[0101] Example 1

[0102] The invention discloses an acid- and alkali-resistant protective film, comprising the following raw materials by weight: 80 kg of PET, 35 kg of PA6, 30 kg of PP, 3 kg of methyl methacrylate-butadiene-styrene copolymer, 1 kg of compatibilizer, 10 kg of nano silicon dioxide, 8 kg of modified polypropylene fiber, 2 kg of pretreated ceramsite, and 12 kg of modified diatomaceous earth; the compatibilizer is maleic anhydride grafted polyolefin.

[0103] The preparation method of the pretreated ceramsite comprises the following steps: crushing 10 kg of ceramsite, calcining at a temperature of 290° C. for 2 hours, and obtaining the pretreated ceramsite, wherein the diameter of the pretreated ceramsite is 0.05-0.08 mm.

[0104] The preparation method of the acid-base resistant protective film comprises the following steps: uniformly stirring PET, PA6, PP, methyl methacrylate-butadiene-styrene copolymer, compatibilizer, nano silicon dioxide, modified polypropylene fiber, pretreated ceramsite and modified diatomaceous earth at a temperature of 95°C, melt-extruding and casting into a film to obtain the acid-base resistant protective film.

[0105] The melting temperature is 180°C; the thickness of the protective film is 0.05 mm.

[0106] The modified polypropylene fiber was prepared according to Preparation Example 1-1, and the modified diatomaceous earth was prepared according to Preparation Example 2-1.

[0107] Example 2

[0108] A kind of acid and alkali resistant protective film, which is different from Example 1 in that, by weight, it comprises the following raw materials: 90kg of PET, 45kg of PA6, 40kg of PP, 5kg of methyl methacrylate-butadiene-styrene copolymer, 3kg of compatibilizer, 15kg of nano silicon dioxide, 12kg of modified polypropylene fiber, 5kg of pretreated ceramsite, and 18kg of modified diatomaceous earth.

[0109] Example 3

[0110] An acid- and alkali-resistant protective film, which differs from Example 1 in that the modified polypropylene fiber adopts Preparation Example 1-2.

[0111] Example 4

[0112] An acid- and alkali-resistant protective film, which differs from Example 1 in that the modified polypropylene fiber adopts Preparation Example 1-3.

[0113] Example 5

[0114] An acid- and alkali-resistant protective film, which differs from Example 1 in that the modified polypropylene fiber adopts Preparation Example 1-4.

[0115] Example 6

[0116] An acid- and alkali-resistant protective film, which differs from Example 1 in that the modified polypropylene fiber adopts Preparation Example 1-5.

[0117] Example 7

[0118] An acid- and alkali-resistant protective film, which differs from Example 1 in that the modified polypropylene fiber adopts Preparation Example 1-6.

[0119] Example 8

[0120] An acid- and alkali-resistant protective film, which differs from Example 1 in that the modified polypropylene fiber adopts Preparation Example 1-7.

[0121] Example 9

[0122] An acid- and alkali-resistant protective film, which differs from Example 1 in that the modified polypropylene fiber adopts Preparation Example 1-8.

[0123] Example 10

[0124] An acid- and alkali-resistant protective film, which differs from Example 1 in that the modified polypropylene fiber adopts Preparation Example 1-9.

[0125] Embodiment 11

[0126] An acid- and alkali-resistant protective film, which differs from Example 1 in that the modified diatomaceous earth adopts Preparation Example 2-2.

[0127] Example 12

[0128] An acid- and alkali-resistant protective film, which differs from Example 1 in that the modified diatomaceous earth is prepared as in Preparation Example 2-3.

[0129] Example 13

[0130] An acid- and alkali-resistant protective film, which differs from Example 1 in that the modified diatomaceous earth is prepared as in Preparation Example 2-4.

[0131] Embodiment 14

[0132] An acid- and alkali-resistant protective film, which differs from Example 1 in that the modified diatomaceous earth is prepared as in Preparation Example 2-5.

[0133] Embodiment 15

[0134] An acid- and alkali-resistant protective film, which differs from Example 1 in that the modified diatomaceous earth is prepared as in Preparation Example 2-6.

[0135] Example 16

[0136] An acid- and alkali-resistant protective film, which differs from Example 1 in that the modified diatomaceous earth is prepared as in Preparation Example 2-7.

[0137] Embodiment 17

[0138] An acid- and alkali-resistant protective film, which differs from Example 1 in that the modified diatomaceous earth is prepared as in Preparation Example 2-8.

[0139] Embodiment 18

[0140] An acid- and alkali-resistant protective film, which differs from Example 1 in that the modified diatomaceous earth is prepared as in Preparation Example 2-9.

[0141] Embodiment 19

[0142] An acid- and alkali-resistant protective film, which differs from Example 1 in that the modified diatomaceous earth is prepared as in Preparation Example 2-10.

[0143] Comparative Example

[0144] Comparative Example 1

[0145] An acid- and alkali-resistant protective film, which differs from Example 1 in that modified polypropylene fiber is not added.

[0146] Comparative Example 2

[0147] An acid- and alkali-resistant protective film, which differs from Example 1 in that an equal amount of polypropylene fibers is used to replace modified polypropylene fibers.

[0148] Comparative Example 3

[0149] An acid- and alkali-resistant protective film, which differs from Example 1 in that modified diatomaceous earth is not added.

[0150] Comparative Example 4

[0151] An acid- and alkali-resistant protective film, which differs from Example 1 in that an equal amount of diatomaceous earth is used to replace the modified diatomaceous earth.

[0152] Comparative Example 5

[0153] An acid and alkali resistant protective film, which differs from Example 1 in that no pretreated ceramsite is added.

[0154] Performance testing

[0155] The acid-base resistant protective films prepared in Examples 1-19 and Comparative Examples 1-5 were subjected to mechanical property tests and wear resistance tests; Mechanical property test: tensile strength and elongation at break were tested according to national standards GB / T 13022-1991 "Test method for tensile properties of plastic films";

[0156] Wear resistance test: On a friction and wear testing machine, the wear resistance of the protective film is measured by the average mass lost per 1000 revolutions of wear.

[0157] The scratch resistance of the coating is measured by placing sandpaper on the coating surface and applying different loads to the sandpaper to determine the minimum mass required to produce a noticeable scratch.

[0158] Tear strength test: The right-angle tear strength was tested according to the method specified in the national standard QB / T 1130-1991; the test results are shown in Table 1.

[0159] Table 1 Test data of embodiments and comparative examples

[0160]

[0161]

[0162] Combining the examples and the data in Table 1, it can be seen that the acid- and alkali-resistant protective films prepared in Examples 1-2, 5, 9, 14 and 18 have good mechanical properties, scratch resistance and wear resistance. Among them, the transverse tensile strength of Example 1 is 88.7 MPa, the longitudinal tensile strength is 91.6 MPa, the elongation at break is 210%, the wear resistance is 0.3 mg, the scratch resistance is 84 g, and the tear strength is 79.2 kN / m, indicating that the protective film prepared in the present application has good tensile strength, tear resistance, scratch resistance and wear resistance, and PET, PA6, PP, modified polypropylene fiber and modified diatomaceous earth and other components have good mechanical strength, tear resistance, wear resistance and scratch resistance, so that the prepared protective film has a good service life.

[0163] The preparation method of modified polypropylene fiber in Example 3 does not add ZIF-8. As can be seen from Table 1, compared with Example 1, the transverse tensile strength is 80.1 MPa, the longitudinal tensile strength is 83.2 MPa, the elongation at break is 185%, the wear resistance is 1.2 mg, the scratch resistance is 75 g, and the tear strength is 71.3 kN / m, indicating that the ZIF-8 of the present application has a high specific surface area, a regular pore structure and wear resistance, and ZIF-8 can be loaded on the surface of the polypropylene fiber, thereby improving the mechanical strength, wear resistance and adsorption of the polypropylene fiber, and subsequently improving the corresponding performance of the protective film.

[0164] Example 4 The preparation method of modified polypropylene fiber does not add modified silver nanowires. As can be seen from Table 1, compared with Example 1, the transverse tensile strength is 75.3 MPa, the longitudinal tensile strength is 78.5 MPa, the elongation at break is 174%, the wear resistance is 1.9 mg, the scratch resistance is 69 g, and the tear strength is 66.4 kN / m, indicating that the modified silver nanowires of the present application have nanoscale size effect, wear resistance and flexibility. The modified silver nanofibers are loaded on the surface of the polypropylene fiber, which improves the flexibility and wear resistance of the polypropylene fiber. The subsequent modified polypropylene fiber is used in the protective film to improve the mechanical properties, flexibility and wear resistance of the protective film, which is conducive to the durable application of the protective film.

[0165] Example 6 changes the mass ratio of polypropylene fiber, ZIF-8 and modified silver nanowires. It can be seen from Table 1 that compared with Example 1, the tensile strength, tear strength, elongation at break, scratch resistance and wear resistance are all worse than those of Examples 1-2 and 5, but better than those of Examples 3-4, indicating that ZIF-8 can be loaded on the surface and pore structure of polypropylene fibers, and the modified silver nanowires can be loaded on the surface and pore structure of polypropylene fibers and ZIF-8. The polypropylene fibers, ZIF-8 and modified silver nanowires cooperate with each other to improve the mechanical properties, wear resistance and antibacterial properties of the polypropylene fibers. The subsequently modified polypropylene fibers are applied to the protective film, thereby improving the corresponding performance of the protective film.

[0166] In the preparation of silver nanowires in Example 7, graphene is not added. As can be seen from Table 1, compared with Example 1, the transverse tensile strength is 77.5 MPa, the longitudinal tensile strength is 80.1 MPa, the elongation at break is 178%, the wear resistance is 1.6 mg, the scratch resistance is 72 g, and the tear strength is 68.9 kN / m, indicating that the graphene of the present application has high strength, large specific surface area and high wear resistance, and the silver nanowires can be loaded on the surface of the graphene, thereby improving the wear resistance and strength of the silver nanowires.

[0167] In the preparation of silver nanowires in Example 8, no silane coupling agent KH570 is added. As can be seen from Table 1, compared with Example 1, the transverse tensile strength is 78.4 MPa, the longitudinal tensile strength is 81.2 MPa, the elongation at break is 180%, the wear resistance is 1.4 mg, the scratch resistance is 74 g, and the tear strength is 70.1 kN / m, indicating that the silane coupling agent of the present application can react with the hydroxyl groups on the surface of the silver nanowires, and also react with the hydroxyl or carboxyl groups on the surface of the graphene, so that the silver nanowires and graphene are closely connected, thereby improving the mechanical strength and wear resistance of the silver nanowires, and subsequently improving the corresponding properties of the polypropylene fiber and the protective film.

[0168] Example 10 changes the mass ratio of silver nanowires, silane coupling agent and graphene. It can be seen from Table 1 that compared with Example 1, the tensile strength, tear strength, elongation at break, scratch resistance and wear resistance are all worse than those of Examples 1-2 and 9, but better than those of Examples 7-8, indicating that the silver nanowires can be loaded on the surface of graphene, and the silane coupling agent reacts with the silver nanowires and graphene respectively, thereby making the silver nanowires and graphene closely connected, improving the mechanical strength and wear resistance of the silver nanowires, and subsequently being applied to the protective film to improve the corresponding performance of the protective film.

[0169] In the preparation method of modified diatomite in Example 11, nano-TiO2 is not added. As can be seen from Table 1, compared with Example 1, the transverse tensile strength is 80.5 MPa, the longitudinal tensile strength is 83.7 MPa, the elongation at break is 186%, the wear resistance is 1.1 mg, the scratch resistance is 76 g, and the tear strength is 71.9 kN / m, indicating that the nano-TiO2 of the present application has good mechanical properties and wear resistance, and the nano-TiO2 can be loaded on the surface of diatomite, which improves the mechanical properties and wear resistance of diatomite, and subsequently improves the corresponding performance of the protective film.

[0170] In the preparation method of modified diatomite in Example 12, no titanate coupling agent is added. As can be seen from Table 1, compared with Example 1, the transverse tensile strength is 81.4 MPa, the longitudinal tensile strength is 84.6 MPa, the elongation at break is 188%, the wear resistance is 0.9 mg, the scratch resistance is 78 g, and the tear strength is 72.7 kN / m, indicating that the titanate coupling agent is combined with the surface hydroxyl groups of nano-TiO2 in the form of chemical bonds, thereby improving the dispersibility of nano-TiO2, the titanate coupling agent can react with the surface group hydroxyl groups of diatomite, and the sodium polyacrylate can increase the viscosity of the system, so that the diatomite, nano-TiO2 and titanate coupling agent are tightly bonded, thereby subsequently improving the corresponding properties of the diatomite and the protective film.

[0171] In the preparation method of modified diatomite in Example 13, modified chitosan solution is not sprayed. As can be seen from Table 1, compared with Example 1, the transverse tensile strength is 80.9 MPa, the longitudinal tensile strength is 84.1 MPa, the elongation at break is 187%, the wear resistance is 1.0 mg, the scratch resistance is 77 g, and the tear strength is 72.2 kN / m, indicating that the modified chitosan solution has good film-forming properties and can coat diatomite, further allowing nano-TiO2 to be stably loaded on the surface of diatomite, thereby improving the mechanical strength and wear resistance of diatomite, and is subsequently applied to a protective film in combination with other components to improve the mechanical properties and wear resistance of the protective film.

[0172] Example 15 changes the mass ratio of diatomite, nano-TiO2 and titanate coupling agent. It can be seen from Table 1 that compared with Example 1, the tensile strength, tear strength, elongation at break, scratch resistance and wear resistance are all worse than those of Examples 1-2 and 14, but better than those of Examples 11-12, indicating that titanate coupling can react with diatomite and nano-TiO2, making the connection between diatomite and nano-TiO2 more stable, further improving the mechanical properties of diatomite, and subsequently applied to the protective film, the modified diatomite is mixed with modified polypropylene fiber and nano-silicon dioxide, further improving the adhesion between the components, thereby improving the mechanical strength and wear resistance of the protective film.

[0173] In the preparation method of the modified chitosan solution of Example 16, sodium alginate is not added. As can be seen from Table 1, compared with Example 1, the transverse tensile strength is 82.1 MPa, the longitudinal tensile strength is 85.1 MPa, the elongation at break is 189%, the wear resistance is 0.8 mg, the scratch resistance is 79 g, and the tear strength is 73.1 kN / m, indicating that sodium alginate and chitosan undergo a cross-linking reaction to form a stable gel system, which improves the viscosity of the solution. After the subsequent chitosan film is formed, the stability and mechanical properties of the film are improved.

[0174] In the preparation method of modified chitosan solution of Example 17, nano bamboo fiber is not added. As can be seen from Table 1, compared with Example 1, the transverse tensile strength is 83.2 MPa, the longitudinal tensile strength is 86.3 MPa, the elongation at break is 191%, the wear resistance is 0.6 mg, the scratch resistance is 81 g, and the tear strength is 74.4 kN / m, indicating that the nano bamboo fiber has high strength, high toughness, low density, good corrosion resistance and wear resistance, and can be uniformly dispersed in the gel system of chitosan. After the subsequent chitosan film is formed, the mechanical properties and wear resistance of the film are improved.

[0175] Example 19 changes the mass ratio of chitosan, sodium alginate and nano bamboo fiber. It can be seen from Table 1 that compared with Example 1, the tensile strength, tear strength, elongation at break, scratch resistance and wear resistance are all worse than those of Examples 1-2 and 18, but better than those of Examples 16-17, indicating that ZIF-8 can be loaded on the surface and pore structure of polypropylene fiber, sodium alginate and chitosan undergo cross-linking reaction to form a stable gel system, and the nano bamboo fiber is uniformly dispersed in the gel system of chitosan. After the subsequent polysaccharide film is formed, the mechanical properties and wear resistance of the film are improved, thereby improving the corresponding properties of diatomaceous earth, and subsequently improving the corresponding properties of the protective film.

[0176] No modified polypropylene fiber is added to Comparative Example 1. As can be seen from Table 1, compared with Example 1, the transverse tensile strength is 65.4 MPa, the longitudinal tensile strength is 68.7 MPa, the elongation at break is 164%, the wear resistance is 2.1 mg, the scratch resistance is 62 g, and the tear strength is 56.2 kN / m, indicating that the modified polypropylene fiber is light, high strength, elastic, wear-resistant, corrosion-resistant, high tensile strength and aging resistance. The modified polypropylene fiber is uniformly dispersed in the system, which improves the corresponding properties of the system such as wear resistance and mechanical properties.

[0177] In Comparative Example 2, the modified polypropylene fiber is replaced by an equal amount of polypropylene fiber. As can be seen from Table 1, compared with Example 1, the transverse tensile strength is 70.2 MPa, the longitudinal tensile strength is 73.5 MPa, the elongation at break is 171%, the wear resistance is 1.7 mg, the scratch resistance is 67 g, and the tear strength is 61.4 kN / m, indicating that the modified polypropylene fiber of the present application has good mechanical properties and wear resistance, and cooperates with other components to jointly improve the corresponding performance of the protective film.

[0178] In Comparative Example 3, modified diatomite is not added. As can be seen from Table 1, compared with Example 1, the transverse tensile strength is 66.2 MPa, the longitudinal tensile strength is 69.2 MPa, the elongation at break is 165%, the wear resistance is 2.0 mg, the scratch resistance is 63 g, and the tear strength is 57.4 kN / m, indicating that the modified diatomite has a porous structure, good air permeability and adsorption, and can improve the heat resistance, wear resistance, aging resistance and other properties of the system. Nano-silicon dioxide can be loaded on the surface and pores of modified polypropylene fibers and modified diatomite, thereby improving the strength, wear resistance and scratch resistance of modified polypropylene fibers and modified diatomite. Subsequently, it is evenly mixed with PET, PA6 and PP to improve the mechanical strength and wear resistance of the protective film.

[0179] Comparative Example 4 replaces the modified diatomaceous earth with an equal amount of diatomaceous earth. As can be seen from Table 1, compared with Example 1, the transverse tensile strength is 71.2 MPa, the longitudinal tensile strength is 74.4 MPa, the elongation at break is 173%, the wear resistance is 1.5 mg, the scratch resistance is 69 g, and the tear strength is 62.4 kN / m, indicating that the modified diatomaceous earth in the present application has good mechanical properties and wear resistance, and is combined with modified polypropylene fiber, nano-silicon dioxide and pretreated ceramsite to jointly improve the corresponding properties of the protective film.

[0180] No pretreated ceramsite is added in Comparative Example 5. As can be seen from Table 1, compared with Example 1, the transverse tensile strength is 67.8 MPa, the longitudinal tensile strength is 70.1 MPa, the elongation at break is 167%, the wear resistance is 1.8 mg, the scratch resistance is 65 g, and the tear strength is 62.5 kN / m, indicating that the pretreated ceramsite has a large specific surface area, light weight, high strength, good corrosion resistance and good wear resistance, can be evenly dispersed in the system, improve the wear resistance of the system, and subsequently cooperate with other components to jointly improve the corresponding performance of the protective film.

[0181] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An acid and alkali resistant protective film, characterized in that: The raw materials are as follows: 80-90 parts of PET, 35-45 parts of PA6, 30-40 parts of PP, 3-5 parts of methyl methacrylate-butadiene-styrene copolymer, 1-3 parts of compatibilizer, 10-15 parts of nano silicon dioxide, 8-12 parts of modified polypropylene fiber, 2-5 parts of pretreated ceramsite, and 12-18 parts of modified diatomaceous earth. The preparation method of the pretreated ceramsite comprises the following steps: crushing the ceramsite, calcining the ceramsite at a temperature of 280-300° C. for 1-2 hours, and obtaining the pretreated ceramsite, wherein the diameter of the pretreated ceramsite is 0.05-0.08 mm; The preparation method of the modified polypropylene fiber comprises the following steps: (1) dispersing polypropylene fibers in a sodium hypochlorite solution, soaking for 1-3 minutes, washing with water, and then heating at 200-210° C. for 1-2 hours to obtain pretreated polypropylene fibers; (2) dissolving PVA in deionized water to obtain a PVA solution, and then spraying the solution on the surface of the polypropylene fiber pretreated in step (1) to obtain treated polypropylene fiber, and then dispersing ZIF-8 in methanol, stirring evenly, spraying the solution on the surface of the treated polypropylene fiber, drying, and setting aside; (3) dispersing the modified silver nanowires in an ethanol solution, stirring at a temperature of 50-55° C. for 30-40 minutes, then soaking the polypropylene fiber obtained in step (2) in the ethanol solution of the modified silver nanowires for 60-80 seconds, taking out the polypropylene fiber, and drying it to obtain a modified polypropylene fiber; The modified silver nanowire has a diameter of 70-90 nm and a length of 70-80 μm; The preparation method of the modified diatomite comprises the following steps: (1) Grinding diatomaceous earth, sieving, dispersing in deionized water, adding sodium polyacrylate, stirring for 30-35 minutes, and drying to obtain pretreated diatomaceous earth; (2) dispersing nano-TiO2 in an ethanol aqueous solution, adding a titanate coupling agent, ultrasonicating at a temperature of 55-60°C for 1-1.5 hours, filtering, and drying to obtain treated nano-TiO2; (3) dispersing the diatomite pretreated in step (1) in deionized water, adding the nano-TiO2 treated in step (2), stirring for 1-2 hours, drying, then spraying the modified chitosan solution, drying, and obtaining modified diatomite; The preparation of the modified silver nanowires comprises the following steps: dispersing the silver nanowires in ethanol, ultrasonicating for 15-20 minutes, adding graphene, continuing ultrasonicating, then adding a silane coupling agent, stirring at a temperature of 60-70° C. for 1-2 hours, stirring evenly, and drying to obtain the modified silver nanowires; The preparation method of the modified chitosan solution comprises the following steps: dispersing chitosan in deionized water, adding hydrochloric acid, adjusting the pH to 4-5, stirring for 10-20 minutes to dissolve the chitosan, then adding sodium alginate and nano bamboo fiber, stirring evenly, and obtaining a modified chitosan solution; The length of the nano bamboo fiber is 25-30 μm and the diameter is 10-15 nm.

2. The acid- and alkali-resistant protective film according to claim 1, characterized in that: The mass ratio of the polypropylene fiber, ZIF-8 and modified silver nanowire is 1:0.1-0.3:0.2-0.

5.

3. The acid- and alkali-resistant protective film according to claim 1, characterized in that: The mass ratio of the silver nanowire, the silane coupling agent and the graphene is 1:0.03-0.05:0.6-0.

9.

4. The acid- and alkali-resistant protective film according to claim 1, characterized in that: The mass ratio of the diatomite, nano-TiO2 and titanate coupling agent is 1:0.3-0.5:0.06-0.

08.

5. The acid- and alkali-resistant protective film according to claim 1, characterized in that: The mass ratio of chitosan, sodium alginate and nano bamboo fiber is 1:0.1-0.2:0.06-0.

08.

6. The method for preparing an acid- and alkali-resistant protective film according to claim 1, characterized in that: The method comprises the following steps: uniformly stirring PET, PA6, PP, methyl methacrylate-butadiene-styrene copolymer, compatibilizer, nano silicon dioxide, modified polypropylene fiber, pretreated ceramsite and modified diatomaceous earth at a temperature of 90-95 DEG C, melt-extruding and casting into a film to obtain an acid-base resistant protective film.

Citation Information

Patent Citations

  • PVC (polyvinyl chloride) composite sheet for indoor decoration and preparation method thereof

    CN106751134A

  • Antibacterial and anti-mildew interior wall latex paint

    CN110358373A